RNAi dari Fragmen 3’UTR Gen Penyandi H+ -ATPase Membran Plasma Melastoma malabathricum L. dapat Menghambat Pertumbuhan Tanaman Tersebut - Muzuni, ,; Sopandie, Didy; Suharsono, Utut Widyastuti; Suharsono, , (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2013)
The RNA silencing technique is an effective tool to examine the biological function of the target mRNA in plants. The recent development of GATEWAYTM cloning technology makes it easy to construct the RNAi vectors with trigger sequences and to analyze the function of a target gene. The objective of this research was to construct RNAi including the 3’UTR fragment of the gene coding plasma membrane H+-ATPase from Melastoma malabathricumL., 3’UTRMmpma. RNAi vector had been successfully constructed using GATEWAYTM cloning technology with the 3’UTRMmpma was used as double-stranded RNA (dsRNA) trigger sequence, pENTRTM/D-TOPO®as entry vector, and pANDA plasmid as destination vector. RNAi had been successfully introduced into M. malabathricumL. mediated by A. tumefaciensEHA101 to analyze the function of Mmpma gene in the detoxifying Al stress. Based on the test of transgenic plants tolerance to Al stress showed that in the nutrient solution including 3.2 mM Al (AlCl3.6H2O), the transgenic plants underwent growth suppression especially roots and leaves, whereas non-transgenic plants underwent growth normally. It showed that suppression of Mmpmagene expression by RNAi to M. malabathricumL. caused the plant became sensitive to Al.Keywords: 3’UTRMmpma, A. tumefaciens, Al stress, RNAi vector